Early Imaging Biomarkers of Cartilage Strain After ACL Reconstruction Predict Patient Pain and Altered Knee Loading - Emily Y. Miller; Timothy Lowe; Hongtian Zhu; Woowon Lee; Pablo F. Argote; Danielle Dresdner; James Kelly; Rachel M. Frank; Eric McCarty; Jonathan Bravman; Daniel Stokes; Nancy C. Emery; et al. (Annals of Biomedical Engineering, 2026)
Purpose To investigate temporal evolution of cartilage strain and relaxometry following ACL reconstruction, and examine associations between MRI metrics, pain, and knee loading patterns during gait as potential early markers of cartilage degeneration. Methods Twenty-five participants (15 female, 10 male; mean age 25.6 years) undergoing ACL reconstruction completed MRI assessments at 6 and 12 month post-surgery, including displacement-encoding MRI (intratissue strain) and quantitative relaxometry (T2, T2*, T1ρ). Pain was evaluated using patient-reported outcome scores. Gait analysis quantified knee adduction moment, knee extension moment, and knee flexion moment at 12 months in a subset of patients. Correlations between MRI metrics in cartilage contact regions, patient-reported outcomes, and knee loading were evaluated. Results Between 6 and 12 month post-reconstruction, increased tibial compressive and transverse strains correlated with worsening pain, while increased tibial shear strain associated with reduced pain and improved outcomes. Participants demonstrating greater symptom improvement exhibited higher knee adduction moments, which associated with favorable compositional changes including decreased femoral T1ρ and decreased tibial hydrostatic strain. Higher knee extension moments associated with increased tibial compressive and hydrostatic strain. Conclusion Cartilage strain and T1ρ changes associate with pain and altered loading patterns, suggesting potential as early post-traumatic osteoarthritis markers. The observed links between knee loading patterns and cartilage structural changes highlight beneficial adaptation of the reconstructed knee to mechanical loading, and potential avenues for early therapeutic (gait-modifiable) intervention. Advanced MRI may enable early identification of at-risk patients following ACL reconstruction.